Sensitized Detection of Inhibitory Fragments and Iterative Development of Non‐Peptidic Protease Inhibitors by Dynamic Ligation Screening - Marco F. Schmidt; Albert Isidro‐Llobet; Michael Lisurek; Adeeb El‐Dahshan; Jinzhi Tan; Rolf Hilgenfeld; Jörg Rademann (2008)
A potential anti-SARS drug has been developed by dynamic ligation screening (DLS), by which nucleophilic fragments are directed to the protein's active site by reversible reaction with an aldehyde inhibitor. Their inhibitory effect is detected by competition with a fluorogenic enzyme substrate. With this concept, low-affinity fragments binding specifically to the active site are quickly identified in a functional enzyme assay.